Homogenously hexagonal prismatic AgBiS2 nanocrystals: controlled synthesis and application in quantum dot-sensitized solar cells1. Issue 9 (7th March 2015) - Liang, Na; Chen, Wenlong; Dai, Fang; Wu, Xiangyang; Zhang, Wei; Li, Zhi; Shen, Jingmei; Huang, Shoushuang; He, Qingquan; JiantaoZai; Fang, Nenghu; Qian, Xuefeng
<x xml:space="preserve">Abstract</x> AgBiS2 nanocrystals synthesized in an oleylamine assisted mixed solvent system show better electrocatalytic activity to polysulfide than Pt.